Utilization of Augmented Reality Technology to Improve Learning in Secondary Schools in Bengkulu - Kurniati, Erisa; Ismiyati, Yanti; Vivekanantharasa, Raveenthiran (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study evaluates the effectiveness of using Augmented Reality (AR) technology in improving learning outcomes and student motivation in secondary schools in Bengkulu. This research used a quantitative research design with an experimental approach, and the sample consisted of 120 students divided into experimental groups (60 students) and control groups (60 students). The experimental group used the AR application for 4 weeks, while the control group used conventional methods. The results showed a significant increase in learning outcomes in the experimental group, with an average score of 23 points compared to 5 points in the control group (t = 10.52, p < 0.001). In addition, questionnaire analysis showed that students in the experimental group had a higher level of learning motivation. These findings support the constructivism and self-determination theory, indicating that AR can increase active interaction and student motivation. Although implementation challenges include limited infrastructure and teacher training, this study suggests the development of more affordable AR applications and ongoing training programs. Overall, AR technology has great potential to improve the quality of education in Indonesia.